Drilled to obey? Ex‐military CEOs and financial misconduct - Koch‐Bayram, Irmela F.; Wernicke, Georg (Strategic Management Journal, 2018)
Research Summary : We examine the influence of CEOs' military background on financial misconduct using two distinctive datasets. First, we make use of accounting and auditing enforcement releases (AAER) issued by the U.S. Securities and Exchange Commission (SEC), which contain intentional and substantial cases of financial fraud. Second, we use a dataset of “lucky grants,” which provide a measure of the likelihood of grant dates of CEOs' stock options having been manipulated. Results for both datasets indicate that CEOs who served in the military are less inclined to be involved in fraudulent financial reporting and to backdate stock options. In addition, we find that these relationships are moderated by board oversight (CEO duality and independent directors in the board). Managerial Summary : CEOs who formerly served in the U.S. military are prevalent among U.S. firms. The military puts strong emphasis on the obedience of its personnel. In this study, we test if time spent in the military leads individuals to be more obedient to rules and regulations in the years after they have left the military and become CEOs. Our findings strongly suggest that CEOs who served in the U.S. military are less likely to be involved in financial misconduct. We also find evidence that tougher board oversight strengthens this relationship. Our findings have implications for regulators, auditors, practitioners, and researchers who are interested in determinants of and mechanisms to prevent fraud and stock option backdating.